Timing of arrival and pre-acclimatization strategies for the endurance athlete competing at moderate to high altitudes - Chapman, R. F.; Laymon, A. S.; Levine, B. D. (High Altitude Medicine & Biology, 2013)
With the wide array of endurance sport competition offerings at moderate and high altitudes, clinicians are frequently asked about best practice recommendations regarding arrival times prior to the event and acclimatization guidelines. This brief review will offer data and current advice on when to arrive at altitude and various potential sea level-based pre-acclimatization strategies in an effort to maximize performance and minimize the risk of altitude sickness.